Developments in chemistry and biological application of cotarnine & its analogs. Issue 50 (11th December 2020) - Sahu, S.K.; Behera, P.K.; Panda, S.; Choudhury, P.; Rout, L.
Abstract: Cotarnine is an important organic molecule having tetrahydroisoquinoline core. Cotarnine core exhibits very important biological property. Its biological property changes by correct functionalization of core structure to form new molecules. Herein we describe the developments of chemistry of cotarnine and its derivatives in terms of property, synthesis, reactivity and biological application from scratch to complex core. This review will update the information about cotarnine chemistry and its application for synthesis of different bioactive product. Graphical abstract: Image 1 Highlights: Cotarnine skeleton in tetrahydroisoquinoline alkaloids. Synthesis, reactivity and biological activity of cotarnine and its analog. Chemistry of cotarnine skeleton in noscapine and noscapinoids. Expansion and functionalization of cotarnine ring in noscapine. Functionalization of cotarnine and chiral semi-cotarnine.